On the Natural Growth Quasilinear Elliptic Euler Equations (Journal of Partial Differential Equations, 1991)
In this paper, we consider the eigenvalue problem and the Dirichlet problem of general Euler equations under the natural growth condition.
Keywords: Natural growth; Elliptic Euler equation; Eigenvalue problem; Variational method